Surface properties of nanostructured alginate-based bioprinted patches - Antonio de Nigris; Giuseppe Quero; Giuseppe Peter Vanoli; Luigi Ambrosone (Applied Surface Science Advances)
Gels of alginate/poly-vinyl alcohol, alginate/poly-vinyl alcohol/indocyanine green freely dispersed and alginate/poly-vinyl alcohol/indocyanine green dispersed liposomes were used to bioprint three different patches. Scanning electron microscope images reveal that the crosslinking with calcium chloride has an effect on surface topography, which causes the formation of aggregates, pores and regular asperities. The atomic force microscopy analysis quantifies the pores distribution and measures surface rugosity. The number and surface area of pores is reduced for systems containing free dye and even more for dye-loaded liposomes. A finer scan on surface allowed for the characterization of liposome aggregations on the surface. Their dimensions are identical to those measured in the aqueous dispersions upstream. Furthermore, surface roughness of samples containing free and/or encapsulated dye is significantly reduced. Intrusive chemical species in the gel interact with the matrix and smooth the cross-linking contraction. Planarized measurement of the nanovesicles dimensions disclose that their shape and diameter are preserved, having a peak at 120 nm. Fibre optics reflectance spectra were performed to investigate the interactions between light and the surfaces of the patches. They reveal that liposomes protect the dye from light degradation and aggregation. Transmittance measurements were renormalized to calculate absorbance spectra and compare them with those in aqueous dispersion. Patches with liposomes containing the dye present classical sharp optical spectra centred at 800 nm, similar to the spectrum of a dye-loaded liposomal dispersion in water. Besides, the patch with dye freely dispersed is attenuated and enlarged, suggesting that the dye is forming less responsive stacks.